Peran Guru Dalam Menstimulasi Kemandirian Anak di PAUD Janji Bunda Marbau - apa, kasih makan (PROSIDING SENADIKA : Seminar Nasional Akademik, 2024)
The nutritional needs of pregnant women is a very important component for pregnancy and must be emphasized during pregnancy. The lack of information conveyed during antenatal visits is often not at the forefront of IEC, but rather on the complications that will occur in pregnancy. Adverse effects in the event of nutritional deficiencies include KEK, anemia and danger to the fetus such as IUGR, LBW, etc. Efforts to increase know-ledge about nutrition include health education such as educational activities carried out by disseminating information so that people are aware, know and understand, but are also willing and accustomed to making recommendations related to health and increasing knowledge, skills, and attitudes. of this activity is to provide education about nutrition to pregnant women to increase knowledge of pregnant women. As a result, from about 30 pregnant women who participated in this activity, the pretest and posttest scores were successfully assessed. there was an increase in knowledge, with 23 (76.7%) pregnant women having good knowledge and 23.3% pregnant women having sufficient knowledge about nutrition for pregnant women. Health education about nutrition for pregnant women has been shown to increase mother's knowledge about nutrition in pregnancy.